Stereocontrolled Synthesis of (±)-Grandisol - Bartlett, William R.; Read de Alaniz, Javier; Carlson, Janet L.; Dillon, Maria P.; Edstrom, Eric; Fischer, Derek A.; Goldblum, Adam A; Luedtke, Gregory R.; Paneitz, Gregory W.; Ryter, Kendal; Schulz, Mark; Shepard, Donnie A.; Switzer, Christopher (Synthesis, 2022)
A synthetic approach to grandisol is described. The route to the cyclobutane core relies on an efficient intramolecular [2+2] cycloaddition that establishes the required cis-ring fusion at the adjacent side chains of the cyclobutane ring. Using a new two-step lithium/halide homologation procedure, norgrandisol was efficiently converted into grandisol. This new approach enables the synthesis of grandisol in five steps from commercially available starting material in 22% overall yield.
Keywords: boll weevil; cyclobutene ring; [2+2] cycloaddition; grandisol; photocyclization; homologation